Positive electrode material, electrochemical device, and electronic device
By forming a cladding layer of sulfide, sulfate and bisulfate of metal M on the positive electrode material of the lithium-ion battery, the problem of structural instability of the positive electrode material at high voltage is solved, and higher cycle stability and battery life are achieved.
Patent Information
- Application Number
- CN202311434098.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing lithium-ion battery positive electrode materials have structural instability at high voltages, resulting in problems with the cycling performance and voltage attenuation of the battery, limiting its practical application.
A positive electrode material including an active substance and a coating layer consisting of at least one or more of a composite of sulfide, sulfate and bisulfate of metal M selected from alkali metals and/or alkaline earth metals. The cladding layer is formed by doping and sintering treatment with the active material, stabilizing the crystal structure of the active material and improving the thermal stability of the material.
The structural stability and cyclic stability of the positive electrode material at high voltages are significantly improved, the cycle life of the battery is extended and the voltage attenuation is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of positive electrode materials, and in particular, to positive electrode materials, electrochemical devices and electronic devices. Background Art
[0002] Lithium-ion batteries have been widely used in electronic portable devices, plug-in hybrid vehicles, electric vehicles, wearable electronic products, medical equipment, defense aviation, energy storage and other fields due to their high energy storage capacity. In order to meet the needs of social development, it is urgent to seek lithium-ion batteries with higher energy density and power density, which requires the cathode materials used to have higher specific capacity and higher voltage platform.
[0003] Traditional positive electrode materials LiCoO2, LiMn2O4 and LiFePO4 all provide charge compensation for lithium ion insertion / extraction through transition metal (Mn, Ni, Co) redox. Although they have a higher and more stable charge and discharge platform, their theoretical specific capacity is therefore limited by the number of electrons that can be provided by the unit transition metal redox. In order to obtain higher specific energy, positive electrode materials are developing in the direction of high voltage. As the voltage of current positive electrode materials increases, part of the oxygen on the surface of the positive electrode materials is irreversibly released, and the crystal structure of the positive electrode materials also undergoes a series of irreversible damages. The lattice oxygen is removed, and the first coulombic efficiency and cycle performance of the battery are greatly reduced. The instability of surface oxygen can also lead to continuous structural decay, causing serious voltage decay and capacity decay problems, which limits practical applications.
[0004] Therefore, there is an urgent need to find a positive electrode material to improve the positive electrode interface stability and cycle stability under high voltage. Summary of the invention
[0005] The present application proposes a positive electrode material, an electrochemical device and an electronic device, which can improve the structural stability of the positive electrode material under high pressure and can also improve the cycle stability of the electrochemical device.
[0006] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising: an active substance and a coating layer located on at least a portion of the surface of the active substance, the coating layer comprising a composite of at least one or more of a sulfide of metal M, a sulfate of metal M, and a hydrogen sulfate of metal M, wherein the metal M is selected from alkali metals and / or alkaline earth metals. In some embodiments, the metal M is selected from at least one of Li, Na, K, Mg, and Ca.
[0007] In some embodiments, the active material has an interface doping layer of metal M in a surface area close to the coating layer.
[0008] In some embodiments, the doping concentration of the alkali metal element in the interface doping layer is less than or equal to 3000 ppm. Preferably, the doping concentration of the alkali metal element in the interface doping layer is less than or equal to 1000 ppm.
[0009] In some embodiments, the thickness of the interface doping layer is 1 nm to 30 nm. Preferably, the thickness of the interface doping layer is 1 nm to 10 nm.
[0010] In some embodiments, the doping concentration of the alkali metal in the region from the surface of the active material to a depth of 30 nm gradually decreases.
[0011] In some embodiments, the active material is selected from sodium metal composite oxides or lithium metal composite oxides, and the sodium metal composite oxides or lithium metal composite oxides are layered metal oxides.
[0012] In some embodiments, the chemical formula of the active substance is A a Ni x1 Co y1 M1 z1 O2, wherein 0.95≤a≤1.08, 0≤x1≤1, 0≤y1<1, x1+y1+z1=1; A is selected from Li or Na, and the M1 element includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, Zr, Sr, Ce and La.
[0013] In some embodiments, the active material includes at least one of LiCoO2, LiNiCoMnO2, NaNiFeMnO2, and NaNiCuFeMnO2.
[0014] In some embodiments, the active material is selected from sodium metal composite oxides, and the coating layer includes a composite of at least one or more of potassium sulfide, potassium sulfate, and potassium hydrogen sulfate.
[0015] In some embodiments, the active material is selected from lithium metal composite oxides, and the coating layer includes a composite of at least one or more of sodium sulfide, sodium sulfate, and sodium bisulfate.
[0016] In some embodiments, the coating layer has a thickness of 2 nm to 100 nm.
[0017] In some embodiments, the mass content of the coating layer in the positive electrode material is 0.1 wt % to 5 wt %.
[0018] In some embodiments, the average particle size D of the positive electrode material 50 1μm to 20μm.
[0019] In a second aspect, the present application provides an electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode plate comprises the positive electrode material described in the first aspect, the electrolyte contains fluoride ions, and when the electrochemical device is fully charged, the surface of the positive electrode material also includes a fluoride of a metal M, wherein the metal M is selected from an alkali metal and / or an alkaline earth metal.
[0020] In some embodiments, the concentration of fluoride ions in the electrolyte is 1 mol / L to 5 mol / L.
[0021] In some embodiments, the negative electrode plate includes a negative electrode material, and the negative electrode material includes at least one of graphite, silicon material, silicon oxide material, tin material, tin oxide material or silicon-carbon composite material.
[0022] In some embodiments, the electrolyte includes an electrolyte and an organic solvent, and the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0023] In a third aspect, the present application provides an electronic device, which includes the above-mentioned electrochemical device.
[0024] Compared with the prior art, a coating layer is formed on the surface of the active material, and the coating layer includes at least one or more complexes of metal M sulfide, metal M sulfate, and metal M hydrogen sulfate. The metal M ions in the coating layer can achieve doping of the active material, and a large amount of metal M ion doping can stabilize the crystal structure of the active material; the coating layer can alleviate the mechanical stress caused by the volume change of the active material during charging and discharging, inhibit the occurrence of crystal cracks inside the active material, inhibit the loss of lattice lithium on the surface of the positive electrode material, improve the surface structural stability of the material and inhibit lattice oxygen overflow; in addition, the coating layer can also improve the thermal stability and long-cycle stability of the material. DETAILED DESCRIPTION
[0025] The technical solution provided by the present invention is further described below in conjunction with specific embodiments and comparative examples, but the present application is not limited to the following embodiments.
[0026] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below.
[0027] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0028] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0029] Traditional positive electrode materials LiCoO2, LiMn2O4 and LiFePO4 all provide charge compensation for lithium ion insertion / extraction through transition metal (Mn, Ni, Co) redox. Although they have a higher and more stable charge and discharge platform, their theoretical specific capacity is therefore limited by the number of electrons that can be provided by the unit transition metal redox. In order to obtain higher specific energy, positive electrode materials are developing in the direction of high voltage. As the voltage of current positive electrode materials increases, part of the oxygen on the surface of the positive electrode materials is irreversibly released, and the crystal structure of the positive electrode materials also undergoes a series of irreversible damages. The lattice oxygen is removed, and the first coulombic efficiency and cycle performance of the battery are greatly reduced. The instability of surface oxygen can also lead to continuous structural decay, causing serious voltage decay and capacity decay problems, which limits practical applications.
[0030] Surface modification is an important method to improve the electrochemical properties of lithium-rich materials. According to the reaction conditions, it can be divided into solid-solid method, liquid-solid method and gas-solid method. The solid-solid method is to mix the active material and the metal salt by ball milling, and generally obtain the surface-modified positive electrode material by heat treatment to achieve surface doping or coating. The gas-solid method treats the active material under different atmospheres and temperatures to cause a chemical reaction between the surface of the active material particles and the atmosphere. The contact of the solid-solid method needs to be solved by high-energy ball milling. The power consumed in the treatment process is large. It is not only difficult to obtain a uniform and thin coating layer, but also more likely to destroy the morphology of the original active material particles. Although the gas-solid method has good contact, there are fewer gas-solid selectable atmospheres and lack of flexibility. The liquid-solid method is to mix the active material and the modifying agent in a liquid environment, which can achieve uniform and effective surface modification without destroying the morphology of the active material particles. However, at high cut-off voltages (>4.3V), the above surface modification methods all improve the long-cycle stability of the positive electrode material at the expense of energy density. How to improve the interface stability and cycle stability of the positive electrode material without affecting the energy density of the positive electrode material is still a technical problem that needs to be solved.
[0031] Therefore, the present application provides a positive electrode material, which includes an active substance and a coating layer located on at least a portion of the surface of the active substance, wherein the coating layer includes a complex of at least one or more of a sulfide of metal M, a sulfate of metal M and a hydrogen sulfate of metal M, wherein the metal M is selected from alkali metals and / or alkaline earth metals.
[0032] In the above scheme, a coating layer is formed on the surface of the active material, and the coating layer includes at least one or more complexes of metal M sulfide, metal M sulfate and metal M hydrogen sulfate. The alkali metal ions and / or alkaline earth metal ions in the coating layer can achieve doping of the active material, and a large amount of alkali metal ions and / or alkaline earth metal ions doping can stabilize the crystal structure of the active material; the coating layer can alleviate the mechanical stress caused by the volume change of the active material during charging and discharging, inhibit the occurrence of crystal cracks inside the active material, inhibit the loss of lattice lithium on the surface of the positive electrode material, improve the surface structural stability of the material and inhibit lattice oxygen overflow; in addition, the coating layer can also improve the thermal stability and long cycle stability of the material.
[0033] In some embodiments, the positive electrode material includes secondary particles and / or primary particles, at least part of the surface of the primary particles is coated with a coating layer, and the secondary particles include a plurality of primary particles with a coating layer. It is understood that the secondary particles are aggregates of a plurality of primary particles, that is, a plurality of primary particles are closely combined to form secondary particles with a dense internal structure. The positive electrode material of the present application may include only primary particles, or only secondary particles, or a mixture of primary particles and secondary particles.
[0034] In some embodiments, the interior of the secondary particle is a dense structure, and the secondary particle is spherical or quasi-spherical.
[0035] As an optional technical solution of the present application, the metal M is selected from at least one of Li, Na, K, Mg and Ca.
[0036] In some embodiments, the active material is selected from a sodium metal composite oxide having an oxygen element and an M1 element, and a lithium metal composite oxide having an oxygen element and an M1 element, wherein the M1 element includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, Zr, Sr, Ce and La.
[0037] Sodium metal composite oxides and lithium metal composite oxides are both layered metal oxides. Layered metal oxides have a layered structure. Usually, the transition metal and the surrounding six oxygens form an M1O6 octahedral structure to form a transition metal layer. Sodium ions or lithium ions are located between the transition metal layers to form a layered structure in which M1O6 polyhedral layers and NaO6 alkali metal layers are alternately arranged. This layered structure can provide more active sites and enhance the diffusion rate of lithium ions. The doping of alkali metal ions and / or alkaline earth metal ions can expand the interlayer spacing between the polyhedral layer and the alkali metal layer in the layered structure, stabilize the crystal structure, and at the same time, improve the interface dynamics of the material.
[0038] Specifically, the chemical formula of the sodium metal composite oxide may be Na xM1O2, the chemical formula of lithium metal composite oxide can be Li x M1O2, 0.70≤x≤1.2.
[0039] In a specific embodiment of the present application, the chemical formula of the active substance is A a Ni x1 Co y1 M1 z1 O2, wherein 0.95≤a≤1.08, 0≤x1≤1, 0≤y1<1, x1+y1+z1=1; A is selected from Li or Na, and the M1 element includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, Zr, Sr, Ce and La.
[0040] In some embodiments, the thickness of the interface doping layer is 1 nm to 10 nm, specifically 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 8 nm, 9 nm or 10 nm, etc., and of course, it can also be other values within the above range, which are not limited here. It can be understood that the interface doping layer formed in the surface area of the active material particles close to the coating layer is mainly formed by the thermal diffusion of alkali metals and / or alkaline earth metals into the crystal structure of the active material during the high-temperature heat treatment process. The doping of alkali metal ions and / or alkaline earth metal ions can expand the interlayer distance between metal atoms (such as Li or Na) and O atoms in the oxygen layer and stabilize the crystal structure.
[0041] Specifically, the doping concentration of the metal M in the region from the surface of the active material to a depth of 30 nm gradually decreases, that is, the doping concentration of the metal M in the active material and the coating layer is relatively high.
[0042] In some embodiments, the doping concentration of the metal M in the interface doping layer is less than or equal to 3000ppm, and can be specifically 3000ppm, 2000ppm, 1000ppm, 900ppm, 800ppm, 700ppm, 600ppm, 500ppm, 400ppm, 200ppm, 100ppm or 50ppm, etc., and can be other values within the above range, which are not limited here. Preferably, the doping concentration of the alkali metal element in the interface doping layer is less than or equal to 1000ppm.
[0043] In some embodiments, the thickness of the coating layer is 2nm to 100nm, specifically 2nm, 3nm, 4nm, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm or 100nm, etc., and of course, it can also be other values within the above range, which are not limited here. By controlling the thickness of the coating layer within the above range, the coating force of the coating layer can be effectively utilized to alleviate the mechanical stress caused by the volume change of the active material during the charge and discharge process, inhibit the generation of crystal cracks inside the active material, inhibit the loss of lattice lithium on the surface of the positive electrode material, improve the surface structural stability of the material and inhibit the overflow of lattice oxygen, and also improve the transmission of lithium ions in the positive electrode material.
[0044] In some embodiments, the average particle size D of the positive electrode material is 50 The average particle size is 1 μm to 20 μm, and the specific average particle size can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 15 μm, 18 μm, 19 μm or 20 μm, etc. Of course, it can also be other values within the above range, which are not limited here. If the average particle size is too large, the diffusion path of lithium ions in large-size particles will be longer, and the greater the resistance that needs to be overcome for diffusion, the crystal deformation and volume expansion of the positive electrode active material caused by the embedding process will continue to accumulate, making the embedding process gradually difficult to carry out. Controlling the particle size of the positive electrode active material within the above range can improve the electrochemical kinetics and rate performance during the charge and discharge process, and reduce polarization, so that the battery has a higher specific capacity, coulomb efficiency and cycle performance. It can also ensure that the particle size of the positive electrode active material is not too small, reduce the side reactions on the surface of the material, and effectively inhibit the agglomeration between particles of the positive electrode active material with too small a particle size, so as to ensure that the battery has a higher rate performance and cycle performance.
[0045] The present invention provides a method for preparing a positive electrode material, comprising the following steps:
[0046] Step S10, mixing the active substance with a salt of an organic metal M containing a sulfate group to obtain a composite;
[0047] Step S20, sintering the composite to obtain a positive electrode material.
[0048] In the above technical scheme, the active material is mixed with the organic salt of metal M containing sulfate, and after uniform mixing, the organic salt of metal M containing sulfate is uniformly attached to the surface of the active material particles, and then sintered. During the sintering process, the metal M ions dope the active material, and the metal M ions occupy the metal position in the active material, which can expand the interlayer spacing between oxygen atoms and metal atoms in the layered structure and stabilize the crystal structure. The organic salt of metal M containing sulfate will form at least one or more complexes of metal M sulfide, metal M sulfate, and metal M hydrogen sulfate during the sintering process. These substances are attached to the surface of the active material to form a coating layer, and are tightly combined with the active material. The coating layer can alleviate the mechanical stress caused by the volume change of the active material during the charge and discharge process, inhibit the generation of crystal cracks inside the active material, inhibit the loss of lattice lithium on the surface of the positive electrode material, improve the surface structural stability of the material, and inhibit the overflow of lattice oxygen; in addition, the coating layer can also improve the thermal stability and long cycle stability of the material. Through the coating treatment of the organic salt of metal M containing sulfate, the sulfide of metal M, the sulfate of metal M, and the hydrogen sulfate of metal M can also reduce the grain boundary transmission impedance between the primary particles of the active material, which is beneficial to improving the rate performance of the positive electrode material, and can improve the interface stability and cycle stability of the positive electrode material without affecting the energy density of the positive electrode material.
[0049] The preparation method of the present application is described in detail below with reference to the examples:
[0050] Step S10, mixing the active material with an organic salt of a metal M containing a sulfate group to obtain a composite.
[0051] In some embodiments, the average particle size of the active substance is 1 μm to 10 μm. The average particle size of the active substance can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm, etc., and of course it can also be other values within the above range, which is not limited here.
[0052] In some embodiments, the active material is selected from a sodium metal composite oxide having an oxygen element and an M1 element, and a lithium metal composite oxide having an oxygen element and an M1 element, wherein the M1 element includes at least one of Al, Ni, Co, Mg, Ti, Mn, Fe, Zn, Cu, Nb, Mo, V, Cr or Zr.
[0053] Sodium metal composite oxides and lithium metal composite oxides are both layered metal oxides. Layered metal oxides have a layered structure in which metal ions and oxygen ions are combined through ionic bonds to form a layered structure. This layered structure can provide more active sites and enhance the diffusion rate of lithium ions. The doping of metal M can expand the interlayer spacing between oxygen atoms and metal atoms M1 in the layered structure and stabilize the crystal structure.
[0054] Specifically, the chemical formula of the sodium metal composite oxide may be Na x M1O2, the chemical formula of lithium metal composite oxide can be Li x M1O2, 0.70≤x≤1.2.
[0055] In a specific embodiment of the present application, the chemical formula of the active substance is A a Ni x1 Co y1 M1 z1 O2, wherein 0.95≤a≤1.08, 0≤x1≤1, 0≤y1<1, x1+y1+z1=1; A is selected from Li or Na, and the M1 element includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, Zr, Sr, Ce and La.
[0056] In some embodiments, based on the total mass of the active substance as 100%, the mass content of metal M in the added organic salt of metal M containing sulfate is 100ppm to 5000ppm, specifically 100ppm, 200ppm, 500ppm, 800ppm, 1000ppm, 2000ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm or 5000ppm, etc., and of course, it can also be other values within the above range, which is not limited here.
[0057] In some embodiments, the average particle size of the organic salt of the sulfate-containing metal M is 1 μm to 5 μm, specifically 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, etc., and may be other values within the above range, which is not limited here.
[0058] In some embodiments, the organic salt of the sulfate-containing metal M comprises at least one of alkyl sulfate and alkyl ether sulfate. Preferably, the organic salt of the sulfate-containing metal M comprises at least one of sodium dodecyl sulfate, magnesium dodecyl sulfate, potassium dodecyl sulfate, lithium dodecyl sulfate, calcium dodecyl sulfate, sodium dodecyl ether sulfate, potassium dodecyl ether sulfate, lithium dodecyl ether sulfate and magnesium dodecyl ether sulfate.
[0059] In some embodiments, the metal M in the organic salt of the metal M containing sulfate is selected from at least one of Li, Na, K, Mg and Ca.
[0060] In some embodiments, the raw materials may be mixed to form a mixture by mechanical mixing, specifically by using a high speed mixer or a VC mixer, as long as the raw materials are mixed evenly.
[0061] In some specific embodiments, the organic salt of the metal M containing sulfate and the active material are ball-milled and mixed in a planetary ball mill, and the mixing time is 0.5h to 3h, specifically 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc., but not limited to the listed values, and other values not listed in the numerical range are also applicable. The ball milling speed is 100r / min-200r / min, specifically 100r / min, 120r / min, 130r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min or 200r / min, etc., but not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0062] In some specific embodiments, a wet mixing process may also be used, that is, the organic salt of the metal M containing sulfate and the active substance are dispersed in a solvent, the solvent is removed after mechanical stirring to obtain a mixture, and the mixture is ground and mixed to obtain a composite. Specifically, the method of removing the solvent may be oven drying, freeze drying, stirring evaporation, spray drying, etc., to remove the solvent in the mixture as much as possible. Specifically, the solvent may be water, an alcohol solvent, an ether solvent, etc., which are not limited here.
[0063] In some embodiments, the drying temperature is 80°C to 200°C, and the drying time is 5h to 48h. The drying temperature can be 80°C, 90°C, 100°C, 120°C, 140°C, 150°C, 180°C or 200°C, and the drying time can be 5h, 10h, 12h, 15h, 18h, 24h, 32h, 36h, 40h or 48h, and other values within the above range are also possible, which are not limited here.
[0064] In order to further improve the tightness of the combination between the coating layer and the active material particles and remove relevant impurities in the material, the composite is sintered.
[0065] Step S20, sintering the composite to obtain a positive electrode material.
[0066] In some embodiments, the sintering process is performed in an oxygen-containing atmosphere, and the oxygen-containing atmosphere can be air, oxygen, a mixed gas of oxygen and an inert gas, or the like.
[0067] In some embodiments, the sintering temperature is 300-700°C; specifically, it can be 300°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 680°C and 700°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0068] In some embodiments, the holding time of the sintering treatment is 3h to 10h, and the holding time can be 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., and of course it can be other values within the above range, which is not limited here. Preferably, the sintering temperature is 300 to 600°C, and the secondary heat treatment time is 5h to 8h.
[0069] In some embodiments, the method further comprises the steps of screening and demagnetizing the positive electrode material.
[0070] In some embodiments, the purpose of screening is 200 mesh to 400 mesh, and the specific mesh number of screening can be 200 mesh, 210 mesh, 250 mesh, 280 mesh, 300 mesh, 350 mesh, 380 mesh and 400 mesh, etc. Of course, it can also be other values within the above range, which is not limited here.
[0071] In some embodiments, the demagnetization equipment is any one of a permanent magnetic drum magnetic separator, an electromagnetic iron remover, and a pulsating high gradient magnetic separator. The purpose of demagnetization is to ultimately control the magnetic substance content of the positive electrode material, avoid the discharge effect of the magnetic substance on the lithium-ion battery and the safety of the battery during use.
[0072] The present application also provides an electrochemical device, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the positive electrode comprises the above-mentioned positive electrode material; the electrolyte contains fluoride ions, and when the electrochemical device is fully charged, the surface of the positive electrode material also includes fluoride of metal M, and the metal M is selected from alkali metals and / or alkaline earth metals.
[0073] In some embodiments, the concentration of fluoride ions in the electrolyte is 1 mol / L to 5 mol / L, specifically 1 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L, etc., and of course, it can also be other values within the above range, which are not limited here. It can be understood that when the positive electrode material on the positive electrode plate contacts the electrolyte, at least one of the sulfide of metal M, the sulfate of metal M and the hydrogen sulfate of metal M will react with the fluoride ions in the electrolyte to form the fluoride of metal M. The fluoride of metal M is dispersed on the surface of the positive electrode material particles to form a solid electrolyte film, which can better protect the positive electrode material particles and reduce the occurrence of side reactions between the particles and the electrolyte.
[0074] The positive electrode also includes a binder and a conductive agent. The conductive agent can be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0075] The positive electrode can be prepared according to conventional methods in the art. Usually, the positive electrode active material and the optional conductive agent and binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector. After drying, cold pressing and other processes, the positive electrode is obtained. Due to the use of the positive electrode active material of the first aspect of the present application, the positive electrode of the present application has high comprehensive electrochemical performance and safety performance.
[0076] The negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. For example, the negative electrode current collector includes two opposite surfaces, and the negative electrode active material layer is stacked on either or both of the two surfaces of the negative electrode current collector.
[0077] The negative electrode current collector may be made of copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and a combination thereof.
[0078] The negative electrode active material layer generally includes a negative electrode active material and optionally a conductive agent, a binder and a thickener.
[0079] As an optional technical solution of the present application, examples of the negative electrode active material may include, but are not limited to, at least one of graphite, silicon material, silicon-oxygen material, tin material, tin-oxygen material or silicon-carbon composite material.
[0080] The conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, the binder may be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC), and the thickener may be carboxymethyl cellulose (CMC). However, the present application is not limited to these materials, and the present application may also use other materials that can be used as negative electrode active materials, conductive agents, binders and thickeners of lithium ion batteries.
[0081] The negative electrode can be prepared according to conventional methods in the art. Usually, the negative electrode active material and optional conductive agent, binder and thickener are dispersed in a solvent, which can be deionized water, to form a uniform negative electrode slurry, which is then coated on the negative electrode current collector, and then dried, cold pressed and other processes are performed to obtain the negative electrode.
[0082] There is no particular limitation on the isolation membrane. Any known porous isolation membrane with electrochemical and chemical stability can be selected, for example, a single-layer or multi-layer film of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0083] On the basis of modifying the positive electrode active material, if the electrolyte system is further improved, it can better
[0084] Stabilize the interface of the positive electrode active material, inhibit the side reaction between the positive electrode active material and the electrolyte, thereby reducing the release of lattice oxygen of the positive electrode active material and improving the cycle performance of the electrochemical device.
[0085] Furthermore, the electrolyte includes an electrolyte and an organic solvent.
[0086] As an optional technical solution of the present application, the electrolyte includes an organic solvent, and the organic solvent includes at least one of a carbonate, a carboxylate or a fluorocarboxylate. Optionally, the carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, butylene carbonate or methyl propyl carbonate; Optionally, the carboxylate includes at least one of ethyl formate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, butyl propionate, ethyl butyrate, methyl formate or ethyl propionate; Optionally, the fluorocarboxylate includes at least one of ethyl fluoroformate, ethyl fluoroacetate, propyl fluoroacetate, butyl fluoroacetate, ethyl fluoropropionate, propyl fluoropropionate, butyl fluoropropionate, ethyl fluorobutyrate or methyl fluoroformate.
[0087] As an optional technical solution of the present application, the electrolyte is selected from at least one of lithium hexafluorophosphate LiPF6, lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (abbreviated as LiTFSI), and lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (abbreviated as LiFSI).
[0088] The electrolyte may further include a functional additive, wherein the functional additive is selected from at least one of vinylene carbonate (VC), vinyl sulfate (DTD), propane sultone (PS), fluoroethylene carbonate (FEC), tris(trimethylsilyl) phosphate (TMSP), adiponitrile (ADN), succinonitrile (SN), 1,3,6-hexanetrinitrile (HTCN) or 1,2,3-tris(2-cyano)propane (TCEP).
[0089] By using the above-mentioned positive electrode material and the above-mentioned electrolyte, they cooperate with each other and work together to stabilize the lattice oxygen of the positive electrode material under high voltage, stabilize the structure of the positive electrode material, and improve the cycle stability of the electrochemical device under high voltage.
[0090] As an optional technical solution of the present application, the electrochemical device of the present application further includes a separator disposed between the positive electrode and the negative electrode to prevent short circuit. The present application does not particularly limit the material and shape of the separator used in the electrochemical device, which may be any material and shape disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0091] As an optional technical solution of the present application, the isolation film may include a substrate layer and a coating layer. In some embodiments, the substrate layer is a non-woven fabric, a film or a composite film with a porous structure. In some embodiments, the material of the substrate layer may include or be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. In some embodiments, the material of the substrate layer may include or be selected from polyethylene porous film, polypropylene porous film, polyethylene non-woven fabric, polypropylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film, etc.
[0092] It will be understood by those skilled in the art that the electrochemical device of the present application may be a lithium ion battery or any other suitable electrochemical device. Without departing from the disclosure of the present application, the electrochemical device in the embodiments of the present application includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0093] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0094] Example 1
[0095] A method for preparing a positive electrode material comprises the following steps:
[0096] (1) 3 g of active material lithium cobalt oxide (LiCoO2) powder and 30 mg of sodium dodecyl sulfate were dissolved in 30 mL of deionized water, stirred continuously, slowly evaporated to dryness at 100° C., and ground to obtain a composite.
[0097] (2) The composite was calcined in air atmosphere at 500° C. for 3 h to obtain a positive electrode material.
[0098] The positive electrode material of this embodiment includes an active material LiCoO2 and a coating layer located on the surface of the active material, the coating layer includes sodium sulfide, sodium sulfate and sodium bisulfate, and the thickness of the coating layer is 15 nm.
[0099] Example 2
[0100] A method for preparing a positive electrode material comprises the following steps:
[0101] (1) 3 g of active material lithium cobalt oxide (LiCoO2) powder and 30 mg of sodium dodecyl sulfate were ball-milled in a planetary ball mill at a ball milling speed of 100 r / min for 3 h to obtain a composite.
[0102] (2) The composite was calcined in air atmosphere at 500° C. for 3 h to obtain a positive electrode material.
[0103] The positive electrode material of this embodiment includes an active material LiCoO2 and a coating layer located on the surface of the active material, the coating layer includes sodium sulfide, sodium sulfate and sodium bisulfate, and the thickness of the coating layer is 15 nm.
[0104] Example 3
[0105] A method for preparing a positive electrode material comprises the following steps:
[0106] (1) 3 g of active material sodium nickel iron manganese oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2) powder and 30 mg of dodecyl magnesium sulfate were dissolved in 30 mL of deionized water, and the mixture was stirred continuously and slowly evaporated to dryness at 100°C to obtain a composite.
[0107] (2) The composite was calcined in air atmosphere at 500° C. for 3 h to obtain a positive electrode material.
[0108] The positive electrode material of this embodiment includes active material NaFe 0.5 Ni 0.5 O2 and a coating layer located on the surface of the active material, the coating layer includes magnesium sulfide, magnesium sulfate and magnesium hydrogen sulfate, and the coating layer has a thickness of 25nm.
[0109] Example 4
[0110] The difference from Example 3 is that in step (1), 30 mg of potassium dodecyl sulfate is used instead of 30 mg of magnesium dodecyl sulfate.
[0111] Example 5
[0112] The difference from Example 3 is that in step (1), 30 mg of lithium dodecyl sulfate is used instead of 30 mg of magnesium dodecyl sulfate.
[0113] Example 6
[0114] The difference from Example 1 is that in step (1), 50 mg of sodium lauryl sulfate is used instead of 30 mg of sodium lauryl sulfate.
[0115] Example 7
[0116] The difference from Example 1 is that in step (1), 80 mg of sodium lauryl sulfate is used instead of 30 mg of sodium lauryl sulfate.
[0117] Example 8
[0118] The difference from Example 1 is that in step (1), 100 mg of sodium lauryl sulfate is used instead of 30 mg of sodium lauryl sulfate.
[0119] Example 9
[0120] The difference from Example 1 is that in step (1), LiN i0.8 Co 0.1 Mn 0.1 O2 replaces lithium cobalt oxide (LiCoO2) powder.
[0121] Comparative Example 1
[0122] Lithium cobalt oxide (LiCoO2) powder is directly used as the positive electrode material.
[0123] Comparative Example 2
[0124] Directly use sodium nickel iron manganese oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2) as the positive electrode material.
[0125] Comparative Example 3
[0126] Directly use lithium nickel cobalt manganese oxide (LiN i0.8 Co 0.1 Mn 0.1 O2) as the positive electrode material.
[0127] Performance Test:
[0128] (1) Morphological characteristics of positive electrode materials
[0129] The morphology of the positive electrode material was analyzed using a scanning electron microscope to obtain its scanning electron microscope image.
[0130] (2) Particle size test of positive electrode materials:
[0131] It is convenient to measure using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0132] (3) Specific surface area test of positive electrode materials:
[0133] The nitrogen adsorption specific surface area analysis test method is used for testing and the result is calculated by the BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by a TriStar II specific surface and pore analyzer produced by Micromeritics of the United States.
[0134] (4) Thickness test of the coating layer of the positive electrode material:
[0135] The positive electrode material particles are cut using an ion beam cutter, and then a high-precision electron spectrometer is used to perform element line scanning on the cross section of the cut particles, so that the distribution position and thickness of the coating layer can be calculated based on the line scanning element distribution curve.
[0136] (5) Electrochemical performance test of positive electrode materials
[0137] The electrochemical performance of the prepared positive electrode material was evaluated by using a button half-cell. The specific method is as follows: the positive electrode material, SP and polyvinylidene fluoride (PVDF) were weighed at a mass ratio of 90:5:5, N-methylpyrrolidone was added at a solid content of 50%, and a high-speed disperser was used to adjust the viscous slurry, which was evenly coated on an aluminum foil with a scraper, and after drying in an oven at 80°C, it was rolled and cut into a positive electrode sheet with a diameter of 14 mm. A lithium sheet with a diameter of 16 mm was used as the negative electrode sheet, a Celgard polyethylene PP film was used as the separator, and a carbonate solution of LiPF6 with a concentration of 1 mol / L (the volume ratio of diethyl carbonate / ethylene carbonate was 1:1) was used as the electrolyte, and the assembly was carried out in a glove box filled with argon.
[0138] The LAND battery testing system was used to carry out discharge capacity, first coulombic efficiency and rate performance tests. The reference capacity was set to 200mA / g, the capacity test rate was 0.2C, and the cycle test condition was 1C.
[0139] Table 1. Electrochemical performance test of positive electrode materials prepared in various embodiments and comparative examples
[0140]
[0141] According to the test data of Examples 1 to 9, a coating layer is formed on the surface of the active material, and the coating layer includes at least one or more complexes of alkali metal sulfides, alkali metal sulfates, and alkali metal hydrogen sulfates. The alkali metal ions in the coating layer can achieve doping of the active material, and a large amount of alkali metal ion doping can stabilize the crystal structure of the active material; the coating layer can alleviate the mechanical stress caused by the volume change of the active material during charging and discharging, inhibit the occurrence of crystal cracks inside the active material, inhibit the loss of lattice lithium on the surface of the positive electrode material, improve the surface structural stability of the material and inhibit lattice oxygen overflow; in addition, the coating layer can also improve the positive electrode interface stability and long cycle stability of the material under high pressure.
[0142] Compared with Example 1, in Comparative Example 1, no sulfide of metal M, sulfate of metal M or hydrogen sulfate of metal M is formed on the surface of the active material, and the side reactions between the positive electrode active material and the electrolyte increase, resulting in a decrease in the initial coulombic efficiency of the battery, and during a long cycle, lattice oxygen on the surface of the positive electrode material overflows, the stability of the crystal structure decreases, the positive electrode active material is easily broken, and the cycle performance is greatly reduced.
[0143] In Comparative Example 2 compared to Example 3, no sulfide of metal M, sulfate of metal M or hydrogen sulfate of metal M is formed on the surface of the active material, and the side reactions between the positive electrode active material and the electrolyte increase, resulting in a decrease in the initial coulombic efficiency of the battery, and during a long cycle, lattice oxygen on the surface of the positive electrode material overflows, the stability of the crystal structure decreases, the positive electrode active material is easily broken, and the cycle performance is greatly reduced.
[0144] Comparative Example 3 directly uses lithium nickel cobalt manganese oxide (LiN i0.8 Co 0.1 Mn 0.1 O2), and no coating treatment was performed, and the cycle capacity retention rate under high pressure was only 88.3%. In summary, it can be seen that the coating layer on the surface of the positive electrode active material provided in the present application can effectively improve the positive electrode interface stability and long cycle stability of the positive electrode material under high pressure.
[0145] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes: an active substance and a coating layer located on at least a portion of the surface of the active substance, wherein the coating layer includes a complex of at least one or more of a sulfide of metal M, a sulfate of metal M and a hydrogen sulfate of metal M, wherein the metal M is selected from alkali metals and / or alkaline earth metals.
2. The positive electrode material according to claim 1, characterized in that The metal M is selected from at least one of Li, Na, K, Mg and Ca.
3. The positive electrode material according to claim 2, characterized in that The surface area of the active material close to the coating layer has an interface doping layer of metal M.
4. The positive electrode material according to claim 3, characterized in that The positive electrode material includes at least one of the following features (1) to (3): (1) The doping concentration of the metal M in the interface doping layer is less than or equal to 3000 ppm; (2) The doping concentration of the metal M in the interface doping layer is less than or equal to 1000 ppm (3) The thickness of the interface doping layer is 1 nm to 30 nm; (4) The thickness of the interface doping layer is 1 nm to 10 nm; (5) The doping concentration of the metal M in the region from the surface of the active material to a depth of 30 nm gradually decreases.
5. The positive electrode material according to claim 1, characterized in that The active material is selected from sodium metal composite oxide or lithium metal composite oxide, and the sodium metal composite oxide or lithium metal composite oxide is a layered metal oxide.
6. The positive electrode material according to claim 1, characterized in that The chemical formula of the active substance is A a Ni x1 Co y1 M1 z1 O2, wherein 0.95≤a≤1.08, 0≤x1≤1, 0≤y1<1, x1+y1+z1=1; A is selected from Li or Na, and the M1 element includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, Zr, Sr, Ce and La.
7. The positive electrode material according to claim 1, characterized in that It meets at least one of the following characteristics: (1) The active material includes at least one of LiCoO2, LiNiCoMnO2, NaNiFeMnO2, and NaNiCuFeMnO2; (2) the active material is selected from sodium metal composite oxides, and the coating layer comprises a composite of at least one or more of potassium sulfide, potassium sulfate and potassium hydrogen sulfate; (3) The active material is selected from lithium metal composite oxides, and the coating layer includes a composite of at least one or more of sodium sulfide, sodium sulfate and sodium bisulfate; (4) The thickness of the coating layer is 2 nm to 100 nm; (5) The mass content of the coating layer in the positive electrode material is 0.1wt% to 5wt%; (6) The average particle size D of the positive electrode material 50 1μm to 20μm.
8. An electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode plate comprises the positive electrode material according to any one of claims 1 to 7, and the electrolyte contains fluoride ions; when the electrochemical device is in a fully charged state, the coating layer of the positive electrode material also includes a fluoride of a metal M, and the metal M is selected from an alkali metal and / or an alkaline earth metal.
9. The electrochemical device according to claim 8, characterized in that The concentration of fluoride ions in the electrolyte is 1 mol / L to 5 mol / L.
10. The electrochemical device according to claim 8, characterized in that It meets at least one of the following characteristics: (1) The negative electrode plate includes a negative electrode material, and the negative electrode material includes at least one of graphite, silicon material, silicon-oxygen material, tin material, tin-oxygen material or silicon-carbon composite material; (2) The electrolyte includes an electrolyte and an organic solvent, and the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
11. An electronic device comprising the electrochemical device according to any one of claims 8 to 10.